2001
DOI: 10.1038/83158
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for NF-κB in Gata3 expression and TH2 differentiation in allergic airway inflammation

Abstract: The transcription factor GATA-3 is expressed in T helper 2 (TH2) but not TH1 cells and plays a critical role in TH2 differentiation and allergic airway inflammation in vivo. Mice that lack the p50 subunit of nuclear factor kappa B (NF-kappa B) are unable to mount airway eosinophilic inflammation. We show here that this is not due to defects in TH2 cell recruitment but due to the inability of the p50-/- mice to produce interleukin 4 (IL-4), IL-5 and IL-13: cytokines that play distinct roles in asthma pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
395
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(430 citation statements)
references
References 39 publications
25
395
4
Order By: Relevance
“…Interestingly, mice lacking p50 are unable to mount an asthma-like airway T H 2 response, and do not induce GATA-3 expression during T-cell stimulation under T H 2 differentiating conditions (Das et al, 2001). Consistent with this finding, BCL-3-deficient T cells also fail to undergo T H 2 differentiation.…”
Section: T-cell Responses Mediated By Nf-kbmentioning
confidence: 58%
“…Interestingly, mice lacking p50 are unable to mount an asthma-like airway T H 2 response, and do not induce GATA-3 expression during T-cell stimulation under T H 2 differentiating conditions (Das et al, 2001). Consistent with this finding, BCL-3-deficient T cells also fail to undergo T H 2 differentiation.…”
Section: T-cell Responses Mediated By Nf-kbmentioning
confidence: 58%
“…Although IL-13 is mainly produced by T cells [39,40], several sources of IL-13 have been suggested, including human and mouse NK cells [16,17], NKT cells [41], basophils [25,26] and mast cells [42]. To specifically address the question of which cell populations produce IL-13 during this IL-4/B7-independent in vivo immune response to T. muris, we performed cell sorting and quantitative RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous findings support this concept and further suggest that IL-13 can mediate resistance to T. muris in the absence of both IL-4 signaling and B7 costimulation [8]. These studies indicated either a novel B7-independent pathway of CD4 + T cell differentiation leading to IL-13 but not IL-4 expression or an alternative cell source that can differentiate to produce IL-13 if B7 is blocked and/or IL-4 is neutralized.Although IL-13 is mainly produced by T cells [39,40], several sources of IL-13 have been suggested, including human and mouse NK cells [16,17], NKT cells [41], basophils [25,26] and mast cells [42]. To specifically address the question of which cell populations produce IL-13 during this IL-4/B7-independent in vivo immune response to T. muris, we performed cell sorting and quantitative RT-PCR.…”
mentioning
confidence: 99%
“…The binding of IL-1a and IL1b to the IL-1 type 1 receptor [27] triggers a signaling cascade that results in the activation of NF-jB and AP1. NF-jB-deficient T cells show impaired ability to polarize to Th2-type cells [28] and express GATA-3, a transcription factor known to control Th2 differentiation [29]. Thus, NFjB family members play a critical role in Th2 development.…”
Section: Discussionmentioning
confidence: 99%